Goods Sales Information System Using Website-Based Agile Development Methods (Case Study At XYZ Store) - Wisard Widsly Kalengkongan; Eric Alfonsius; Mahardika Inra Takaendengan (Jurnal Ilmiah Sistem Informasi Akuntansi, 2023)
Goods sales information system is a system that can manage the process of managing the sale of goods from inventory management to the sales process in XYZ Stores. The purpose of this research is to design and create a media that can manage the process of inventory management and website-based sales of goods. This system can make it easier for the research site in terms of the process of managing the goods to be sold. In this study using several research methods such as data collection techniques used are observation, documentation and interview methods as well as testing methods used using the blackbox method. In addition, in developing this system using the agile system development method. The conclusions in this study are the results of the design and manufacture of the existing system both in terms of website display results and from the function of buttons such as login, save, edit and delete buttons resulting in a 95.83% test..